The synthesis of some coumestan and related chromogenic derivatives of crown ethers, part II - (:unkn) unknown (SPRINGER, 1998)
The [18]crown-6 derivatives of 8,9-dihydroxy-6H-benzofuro[3,2-c] [I]benzopyran-6-one, 1,3-dimethyl-8,9-dihydroxy-6H-benzofuro[3, 2-c][1] benzo pyran-6-one, 6,7-dihydroxy-3,4-dihydro-2H-dibenzofuran-1-one and 6,7-dihydroxy-3, 3 -dimethyl-3,4-dihydro-2H-dibenzofuran-1-one, were prepared from o-dihydroxy compounds, and polyethylene glycol ditosylates in the presence of K2CO3/CH3CN/H2O. Some coumestan related 3-5 oxygen containing heterocyclic-crowns were also synthesized The structures were identified by elemental analysis, H-1-NMR, C-13-NMR, IR spectra and CI mass spectra.
Keywords: macrocyclics; chromogenic compounds; molecular recognition; COUMARIN